Perbandingan Jenis Media Tanam dengan Sistem Aquaponik Terhadap Pertumbuhan dan Hasil Melon Madu (Cucumis melo L.) - Siregar, Maimunah (JURNAL AGROPLASMA, 2024)
The aquaponic plant cultivation system is used to utilize narrow urban land in order to increase urban agricultural production. The aim of the research is to determine the effect of comparing types of planting media with an aquaponic system on the growth and yield of honey melon plants (Cucumis melo L.). This research used a non-factorial Complete Randomized Design, with 4 treatment and 5 replication with the factors studied was the comparison of several types of planting media for the "M" aquaponic system consisting of M1 = 50% sludge planting media + 50% rice husk charcoal, M2 = 50% cocopeat planting medium + 50% rice husk charcoal, M3 = 50% tankos planting medium + 50% rice husk charcoal, M4 = 50% filter cake planting medium + 50% Rice Husk Charcoal. The parameters observed were plant length (cm), stem diameter (cm), number of leaves (strands), flowering age (days), fruit weight per treatment (kg), fruit diameter (cm). The results of the research showed that the comparative effect of several types of planting media in the aquaponic system had a positive effect on the parameters of plant length (cm), stem diameter (cm), number of leaves (strands), flowering age (days), fruit weight (kg), and fruit diameter ( cm) with the best treatment on M1 (50% sludge planting medium + 50% rice husk charcoal). Keywords: aquaponics, planting media, honey melon